2017
DOI: 10.4012/dmj.2016-313
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the calcium-sensing receptor in mineral trioxide aggregate-induced osteogenic gene expression in murine MC3T3-E1 cells

Abstract: Mineral trioxide aggregate (MTA) has excellent biocompatibility as well as bioactivity, including an ability to induce osteoblast differentiation. We examined the effects of the calcium-sensing receptor (CaSR) on osteogenic gene expression induced by MTA. MC3T3-E1 cells were cultured with or without (control) MTA. The expression levels of Runx2, type I collagen, and CaSR genes were analyzed by real-time polymerase chain reaction and their products were measured using enzyme-linked immunosorbent assays. The lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…This is attributed to the suitable pH and calcium ions levels in NSY-224(60). It has been reported that calcium ions stabilize or enhance the viability of dental pulp cells [ 44 ], periodontal ligament cells [ 45 ], and odontoblasts [ 46 ]. Additionally, pH is also an important factor that influences the wound healing process by changing throughout the process [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is attributed to the suitable pH and calcium ions levels in NSY-224(60). It has been reported that calcium ions stabilize or enhance the viability of dental pulp cells [ 44 ], periodontal ligament cells [ 45 ], and odontoblasts [ 46 ]. Additionally, pH is also an important factor that influences the wound healing process by changing throughout the process [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, Chatopadhyay et al showed that inactivation of CaSR decreased rat calvarial osteoblast proliferation and differentiation 55. Mechanistically, the activation of CaSR directly stimulated RUNX-2 expression, which is referred to as the master switch of osteogenic differentiation due to its targeting of the transcription of osteoblast-related genes such as those encoding osteocalcin (OCN), type I collagen, and ALP 56-58. Among these factors, OCN and type I collagen are the main constituents of bone extracellular matrix (ECM) and ALP is responsible for mineralisation of the ECM 58.…”
Section: Resultsmentioning
confidence: 99%
“…The CaSR belonging to the G protein‐coupled receptors can sense the extracellular Ca 2+ concentration and instantaneously mobilize intracellular Ca 2+ flux 68 . Previous studies have shown that CaSR signals mediate the osteogenic differentiation of BMSCs in vitro and bone formation in vivo, and CaSR agonists can promote the proliferation, differentiation and matrix mineralization of osteoblasts 41,69,70 . In addition, Ca 2+ influx caused by mechanically sensitive channels also promotes osteogenic differentiation 71 ; Orai1 gene knockout leads to impaired osteoblast differentiation and mineralization 43 …”
Section: Ca2+/can/nfat Signalling Pathway In Osteoblastogenesismentioning
confidence: 99%